Mental and Social Health of Children and Adolescents With Pre-existing Mental or Somatic Problems During the COVID-19 Pandemic Lockdown - Zijlmans, Josjan; Teela, Lorynn; van Ewijk, Hanneke; Klip, Helen; van der Mheen, Malindi; Ruisch, Hyun; Luijten, Michiel A. J.; van Muilekom, Maud M.; Oostrom, Kim J.; Buitelaar, Jan; Hoekstra, Pieter J.; Lindauer, Ramón; et al. (Frontiers in Psychiatry, 2021)
Background: The COVID-19 lockdown increases psychological problems in children and adolescents from the general population. Here we investigate the mental and social health during the COVID-19 lockdown in children and adolescents with pre-existing mental or somatic problems. Methods: We included participants (8-18 years) from a psychiatric (N = 249) and pediatric (N = 90) sample, and compared them to a general population sample (N = 844). Measures were assessed during the first lockdown (April-May 2020) in the Netherlands. Main outcome measures were Patient-Reported Outcomes Measurement Information System (PROMIS®) domains: Global Health, Peer Relationships, Anxiety, Depressive Symptoms, Anger, and Sleep-Related Impairment. Additionally, socio-demographic variables, COVID-19-related questions, changes in atmosphere at home from a parent and child perspective, and children’s experiences of lockdown regulations were assessed. Results: On all measures except Global Health, the pediatric sample reported least problems. The psychiatric sample reported significantly more problems than the general population sample on all measures except for Anxiety and Peer Relationships. Having a COVID-19 affected friend/relative and a COVID-19 related change in work situation negatively moderated outcome, but not in the samples with pre-existing problems. All parents reported significant decreases in atmosphere at home, as did children from the general population. Conclusion: We observed significant differences in mental and social health between three child and adolescent samples during the COVID-19 pandemic lockdown and identified COVID-19-related factors influencing mental and social health.